STUDENT’S PERCEPTION OF BBC ENGLISH YOUTUBE CHANNEL FOR LEARNING VOCABULARY MASTERY - Meita Lesmiaty Khasyar; Annisa Lutfi Sabila (Prodi Pendidikan Bahasa Inggris, STKIP Muhammadiyah Bogor, 2020)
This research was qualitative research. The objective of the research was to investigate student’s perception of BBC English YouTube Channel for learning vocabulary mastery. The subject of the research was tenth grade students of SMK Putra Pelita, located in Cibitung Tengah-Tenjolaya. There were 10 participants in this research. The data collecting technique used by the writer were questionnaire and interview. The writer did the research by sharing questionnaire in form of Google form. The result showed that students felt easier when learning English by watching video. The participant agreed that BBC English Channel video was easy to understand because the pronunciation was clear. Then, the participant can learn a lot of vocabulary that they did not know before after watch the video. It also increase their language aspect especially grammar. Besides, the result of the questionnaire and interview showed that the result was positive. Participants agreed that using BBC Channel on YouTube can help them in learning vocabulary mastery. Furthermore, this media can be an alternative way for teacher to teach English especially vocabulary mastery. Thus it can be concluded that learning vocabulary mastery using BBC English YouTube channel has proven to be effective in increasing students’ vocabulary mastery.